Semele - Eccles, John 1668-1735; Rooley, Anthony (Florida Seminola productions, 2003)
Semele is an opera by John Eccles. The libretto is by William Congreve, drawing on the Greek myth of Semele. The opera was written in 1707, but was never performed in Eccles's lifetime; in fact, the work was not performed until 22 April 1972 when it was given at St John's, Smith Square in London. There was an earlier semi-staged performance given in The Holywell Music Room June 4-6 1964 by the Oxford University Opera Club and Wadham Music Society, conducted by John Byrt - also claiming to be the 'World Premiere'.Eccles's work should not be confused with the 1744 opera Semele by George Frideric Handel, also based upon Congreve's libretto. There is also an opera Sémélé, on the same theme, by Marin Marais.